Back on Track - Cleto, Fabio (Elephant & Castle, 2024)
This paper addresses the current nostalgia mode, from the most diverse areas of merchandising and cultural production to the very contours of today’s ‘connected’ sociality. Current nostalgia seems to impede creativity and the very idea of a future, which would appear to be unthinkable without being filtered by the the sepia lens of a cosmetic vision of the past. In TV programs, cinema, fashion or advertisement, cars or pop music, our time is the time of quotation, revival, and remake. It is a zombie time in which the future coincides with the generational time one regrets the loss of. It is a cosmetic time of hyperkinetic immobility, in which the future is a retro concept – a time that deprives subjectivity back into a full sense of its contemporaneity.